2017
DOI: 10.1016/j.addma.2016.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of in situ controlled heat treatment (ISHT) of Inconel 718 during electron beam melting additive manufacturing

Abstract: A novel technique was developed to control the microstructure evolution in Alloy 718 processed using Electron Beam Melting (EBM). In situ solution treatment and aging of Alloy 718 was performed by heating the top surface of the build after build completion scanning an electron beam to act as a planar heat source during the cool down process. Results demonstrate that the measured hardness (478±7 HV) of the material processed using in situ heat treatment similar to that of peak-aged Inconel 718. Large solidifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 32 publications
3
41
0
Order By: Relevance
“…In the upper part of the build, the solidification becomes predominantly equiaxed with a random orientation of the grains. This evolution has been pointed out by Kirka et al [19] in the case of the electron beam-melting of IN718. It is also confirmed using the G/R diagram of solidification for IN718 [20] and the model developed by Renderos et al [21].…”
Section: Interpretationssupporting
confidence: 55%
“…In the upper part of the build, the solidification becomes predominantly equiaxed with a random orientation of the grains. This evolution has been pointed out by Kirka et al [19] in the case of the electron beam-melting of IN718. It is also confirmed using the G/R diagram of solidification for IN718 [20] and the model developed by Renderos et al [21].…”
Section: Interpretationssupporting
confidence: 55%
“…An in situ controlled heat treatment was attempted, by scanning the top surface of the build after the process was finished, to homogenize and age the microstructure, but resulted in cracks and poor tensile performance [188]. Efforts have also been put in identifying process-microstructure relationship, showing that besides the higher density and better surface finish, the controlled tailoring of grain structures and crystallographic textures can be achieved by adjusting the scan strategies [62,76,78,189,190].…”
Section: Ebm In718mentioning
confidence: 99%
“…It is important to note that both the Laves phase and the hardening phases γ and γ" consume niobium for their formation. The dissolution temperature of the Laves phase is between 982 and 1093 • C [43], while γ and γ" precipitates form during the cooling phase at about 900 • C [44]. As already detailed above, it can be concluded that during the build, the temperatures within the strut deviated significantly from the bulk, eventually leading to the different appearance of the microstructure within the struts.…”
Section: Microstructurementioning
confidence: 72%